O Estado como parte da república - Cicero Araujo (Universidade do Estado do Rio de Janeiro, 2012)
The main objective of this article is to analyze an ideal of civic life, the Republic, based on the form of the sovereign state. Historically, the convergence between Republic and sovereign state has been truncated by the former's commitment to the thesis of royal absolutism. However, as the democratic issue (translated in the values of equality and pluralism) was absorbed by sovereignism, such convergence became more plausible. As viewed in this article, the theoretical bridge of that passage is the concept of political representation. The issue is thus to show in what way a certain vision of the political form (that of the state) can fit into a theory of political representation that contemplates the above-mentioned values.